Pengaruh Terapi Ice Cube untuk Mengurangi Haus Pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di RSU Royal Prima Medan - Kaniya, Putri; Setiawan, Ika; Zahra, Khairani; Manalu, Filius Gratcia; Nasution, Anggina Putri; Kaban, Karmila Br (Universitas Malahayati, 2024)
ABSTRACT Kidney failure is a condition where the functioning of the kidneys decreases suddenly. This occurs when the kidneys are unable to release substances into body fluids that are excreted from the body. This disrupts hormone function and metabolism, body fluids, electrolytes and phosphates (Harmilah, 2020). This kind of research is known as quantitative research. The population of this study was 134 patients at RSU Royal Prima Medan with chronic kidney failure. This sample was taken using an accidental sampling technique. The aim of this study was to investigate the provision of ice cube therapy before starting ice cube therapy, chronic kidney failure sufferers should reduce thirst. The majority The thirst level before undergoing ice cube therapy was 80 (moderate thirst category), and the average thirst level after being given ice cube therapy was 70 (light thirst category). This finding is based on the results of the Wilcoxon Test. Therefore, the p-value obtained is 0.000 (p0.05) for decreasing the intensity of thirst, it appears that the hypothesis (Ho) is accepted. Patients are advised to regularly apply this ice cube therapy to relieve thirst. The results of our research regarding